2021
DOI: 10.1002/hyp.14203
|View full text |Cite
|
Sign up to set email alerts
|

Issues in generating stochastic observables for hydrological models

Abstract: This paper provides a historical review and critique of stochastic generating models for hydrological observables, from early generation of monthly discharge series, through flood frequency estimation by continuous simulation, to current weather generators. There are a number of issues that arise in such models, from uncertainties in the observational data on which such models must be based, to the potential persistence effects in hydroclimatic systems, the proper representation of tail behaviour in the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 134 publications
(157 reference statements)
0
17
0
Order By: Relevance
“…In our special issue, all three papers dealing with input uncertainty similarly focus largely on precipitation uncertainty. The papers investigate input (precipitation) uncertainty and its impact on parameter identification in hydrological models (Liu et al, 2021), input uncertainty in observed and generated variables for hydrological models and process representation (Beven, 2021b), and precipitation uncertainty impact on the rainfall‐triggered landslide events (Culler et al, 2021). Beven (2021b) also discusses uncertainties in other input variables, that is, temperature and evapotranspiration.…”
Section: Impact Of Observational Uncertainty On Process Representatio...mentioning
confidence: 99%
“…In our special issue, all three papers dealing with input uncertainty similarly focus largely on precipitation uncertainty. The papers investigate input (precipitation) uncertainty and its impact on parameter identification in hydrological models (Liu et al, 2021), input uncertainty in observed and generated variables for hydrological models and process representation (Beven, 2021b), and precipitation uncertainty impact on the rainfall‐triggered landslide events (Culler et al, 2021). Beven (2021b) also discusses uncertainties in other input variables, that is, temperature and evapotranspiration.…”
Section: Impact Of Observational Uncertainty On Process Representatio...mentioning
confidence: 99%
“…The HK dynamics are also linked to the entropy maximization principle, and thus, to robust physical justification [8]. It is worth noting that the stochastic simulation of the HK dynamics is still a mathematical challenge [9] since it requires the explicit preservation of high-order moments in a vast range of scales [10,11], affecting both the intermittent (fractal) behavior in small scales [12] and the dependence in extremes [13].…”
Section: Hk Clusteringmentioning
confidence: 99%
“…of high-order moments in a vast range of scales [10,11], affecting both the intermittent (fractal) behavior in small scales [12] and the dependence in extremes [13]. Hurst-Kolmogorov (HK) dynamics present in the annual minimum water level of the Nile River as a result of the perpetual change of Earth's climate, and as compared to a roulette timeseries resembling a white noise process.…”
Section: Hk Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Stochastic modelling and issues in surface hydrology were provided by Yevjevich (1974), Klemeš (1978), Yevjevich (1987), Wright et al (2020) and Beven (2021). A futuristic opinion on hydrological modelling, including stochastic approaches, was discussed by Yevjevich (1991).…”
mentioning
confidence: 99%